MENINGKATKAN PENJUALAN DENGAN CUSTOMER ACQUISITION COST - Suwandi Suwandi; Melinda Melinda; Ana Rusmardiana; A. Besse Dahliana; Arfiani Yulianti Fiyul; Teuku Fajar Shadiq; Abdullah Abdullah; Joko Rehutomo (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The company's operational conditions in Indonesia are still not optimal, so as a result they have not been able to increase their sales every period. This ex post facto study aims to examine the effect of customer acquisition cost on increasing sales in the cosmetics and household sub-sector industrial companies on the Indonesia Stock Exchange for the 2016-2021 period. This study involved 10 companies and as many as 5 companies were selected as research samples. Thus, obtained 30 observational data based on purposive sampling technique. Secondary data in the form of company financial statements were collected through the www.idx.co.id page using documentation techniques. The data that has been collected is then analyzed using simple linear regression and processed using the SPSS 23 program. The results show that customer acquisition costs have a positive and insignificant effect on increasing sales. Following up on these findings, the initial assessment of customer acquisition costs by companies on the Indonesia Stock Exchange needs to be carried out more optimally so that it can encourage an increase in company sales